The lungs and respiratory system - Finance, Charles L.; Finance, Charles L.; Hicks, Carolyn B.; Hicks, Carolyn B.; Castle, Nick; Castle, Nick (Videoteca primaria I. Fisiologia humana I, 1975)
Presenta la respiración y la función de los pulmones.